2021
DOI: 10.3758/s13421-020-01130-5
|View full text |Cite|
|
Sign up to set email alerts
|

The visual and semantic features that predict object memory: Concept property norms for 1,000 object images

Abstract: Humans have a remarkable fidelity for visual long-term memory, and yet the composition of these memories is a longstanding debate in cognitive psychology. While much of the work on long-term memory has focused on processes associated with successful encoding and retrieval, more recent work on visual object recognition has developed a focus on the memorability of specific visual stimuli. Such work is engendering a view of object representation as a hierarchical movement from low-level visual representations to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 66 publications
3
31
0
Order By: Relevance
“…The visual model was created by feeding the object images through the DNN, extracting the activation values from layer 2, and correlating the values between the stimuli resulting in a 240 x 240 similarity matrix. This was then turned into a dissimilarity matrix by computing the pairwise dissimilarity values as 1 – Pearson’s correlation, resulting in the final visual model. Construction of the semantic feature RDM followed Clarke and Tyler (2014) but used updated property norms (Hovhannisyan et al, 2021). We first computed pairwise feature similarity between concepts from a semantic feature matrix in which each concept is represented by a binary vector indicating whether a given feature is associated with the concept or not.…”
Section: Methodsmentioning
confidence: 99%
“…The visual model was created by feeding the object images through the DNN, extracting the activation values from layer 2, and correlating the values between the stimuli resulting in a 240 x 240 similarity matrix. This was then turned into a dissimilarity matrix by computing the pairwise dissimilarity values as 1 – Pearson’s correlation, resulting in the final visual model. Construction of the semantic feature RDM followed Clarke and Tyler (2014) but used updated property norms (Hovhannisyan et al, 2021). We first computed pairwise feature similarity between concepts from a semantic feature matrix in which each concept is represented by a binary vector indicating whether a given feature is associated with the concept or not.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Störmer (2020, 2021) demonstrated that the meaningfulness of to be remembered stimuli, that is, the ability of these stimuli to be recognized as everyday objects, human faces, etc., boosts VWM capacity and that this boost cannot be explained solely by perceptual differences between meaningful and meaningless stimuli (Asp et al, 2021). Based on these findings, we suggest that conceptual distinctiveness, along with perceptual similarity (Hovhannisyan et al, 2021;Hu, Liu, Song, Wang, & Zhao, 2020;Napsi et al, 2020;Otsuka, Nishiyama, Nakahara, & Kawaguchi, 2013;Xie & Zaghloul, 2021), can also be an important determinant of VWM for real-world objects.…”
Section: Distinctiveness In Memory For Objectsmentioning
confidence: 73%
“…The organization of a CNN, in which internal "hidden" layers of nodes feed information forward to a final output layer, has parallels with the organization of the human visual system (Yamins & DiCarlo, 2016), in which representations shift from more basic visual features to higherlevel object categorization as one moves from posterior to anterior regions (Coutanche et al, 2016). Recently, studies of memorability have been extended to semantic features, finding that the interrelatedness of item features positively predicts hit rates on visual and lexical memory tests (Hovhannisyan et al, 2021). Interestingly, hit rates are correlated across tests, suggesting some similarity in the basis for perceptual and conceptual memory traces.…”
Section: Episodic Memories Of Percepts and Conceptsmentioning
confidence: 99%